Autoridade docente na educação infantil: relações de poder e processos de (des)naturalização - Reichert, Estela Elisabete (Universidade do Vale do Rio dos Sinos, 2015)
This dissertation investigates the processes of constitution of certain meanings of teacher authority in Children Education in Contemporaneity. The theoretical field on which this research has been based - Post-Structuralism - has provided the tools to identify and describe power relations that take part in the process of signifying teacher authority in contemporary education relationships. The investigation has involved a field work based on ethnographical principles. I followed up a Level III Children Education group for four months recording data on a notebook; I coordinated a focal group with fifteen 5-6 year-old children; and interviewed the teacher in charge of that group. The last two procedures were performed in order to complement information obtained along the observations. To construct the analytical units, I organized the empirical material by using the concepts of authority and power, in an attempt to describe and analyze two power technologies - affection and care - which operate on the constitution of certain meanings of teacher authority. By doing so, I have tried to show that teacher authority in Children Education is constituted of affection and care practices defined in the adult-child relationship, particularly in the relationship established between the teacher and the group of students. It is possible to evidence that care and affection have emerged as essential attributes of teacher performance, mainly in the constitution and naturalization of a form of female teacher authority in Children Education - the affective and regardful teacher. Moreover, we can consider that affection and care (understood from a naturalized perspective) are regarded as conditions to teach children, while specific academic education is given lower priority. Finally, we can evidence that such power technologies operate on the conduction of conducts of children in both educational relationships and ways of exercising teacher authority.
Keywords: Autoridade docente; Poder; Educação infantil; Afeto; Cuidado; Teacher authority; Power; Children education; Affection; Care; ACCNPQ::Ciências Humanas::Educação